The impact of the digital ruble on the resource base of Russian banks - A. V. Berdyshev (Вестник университета, 2021)
The article considers the economic nature of the new form of Russian money, the issue of which, in addition to the already existing cash and non-cash money, was announced by the Bank of Russia in October 2020. The issues of the influence of the digital ruble on the activities of commercial banks have been investigated. Based on the analysis of the structure of the banking sector’s liabilities to legal entities and individuals, it has been determined that the launch of the digital ruble will provoke an outflow of about 15 % of funds from the current accounts of customers, which, given the use of stable balances on these accounts as a source of financing of income generating assets, will cause the need for banks to increase their interest rates on the credit market.